2021
DOI: 10.1038/s41598-021-88961-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage morphological plasticity and migration is Rac signalling and MMP9 dependant

Abstract: In vitro, depending on extracellular matrix (ECM) architecture, macrophages migrate either in amoeboid or mesenchymal mode; while the first is a general trait of leukocytes, the latter is associated with tissue remodelling via Matrix Metalloproteinases (MMPs). To assess whether these stereotyped migrations could be also observed in a physiological context, we used the zebrafish embryo and monitored macrophage morphology, behaviour and capacity to mobilise haematopoietic stem/progenitor cells (HSPCs), as a fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…In our study, VRICs showed an ameboid movement pattern on the retinal surface and along blood vessels. 26 This is aligned with their critical immune patrolling and response functions, as well as chasing chemotactic signals and revealing an increase in shape plasticity, which confirmed the outcome of previous studies performed in vitro. 27 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, VRICs showed an ameboid movement pattern on the retinal surface and along blood vessels. 26 This is aligned with their critical immune patrolling and response functions, as well as chasing chemotactic signals and revealing an increase in shape plasticity, which confirmed the outcome of previous studies performed in vitro. 27 …”
Section: Discussionsupporting
confidence: 88%
“…The x - and y -planes are the only ones explored in our manuscript, as we currently have no information on the z -plane that might identify VRICs through the neuroretinal layers. 26 Although it might be perceived as marginal, this biodynamic aspect may significantly contribute to defining the macrophage migration dynamic, clarifying whether they adopt a prevalent ameboid or mesenchymal migratory pattern or behave differently depending on the plane that they interact with. In addition, the potential migration toward the retinal pigment epithelium might lead to further hypotheses on the interplay of VRICs with the choroidal immune compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix Metalloproteinases (MMPs) are a critical component of macrophage migration. Among many MMPs, MMP9 has been suggested to be required for macrophage migration and phagocytosis (Gong et al, 2008; Travnickova et al, 2021). Therefore, we hypothesized that the differential MMP9 requirement governs migratory behavior between amoeboid/metaphocytes and dendritic macrophages in zebrafish skin.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages can infiltrate most tissues and migrate between cells in vivo by degrading extracellular matrix (ECM) with extracellular proteinases such as matrix metalloproteinases (MMPs), cathepsins, and urokinase-type plasminogen activator (Verollet et al, 2011). A few studies have shown that MMP9 activity is critical in macrophage migration in mice and zebrafish (Gong et al, 2008; Travnickova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Murine RAW264.7 macrophages or primary human alveolar macrophages cultured on less rigid substrates display a more rounded shape compared to those cultured on a more rigid substrate ( Patel et al, 2012 ). Such morphological adaptations may be highly relevant in the movement of macrophages, which adopt different migration modes in response to environmental constraints ( Van Goethem et al, 2010 ; Vérollet et al, 2011 ; Travnickova et al, 2021 ).…”
Section: The Role Of Mechanical Stimuli On Macrophagesmentioning
confidence: 99%